Establishment and Evaluation of a Dynamic Pressure Measuring and Analysis System for the Air Dense Medium Fluidized Bed. (2015) - Sheng, Cheng; Zhao, Yuemin; Duan, Chenlong; Zhang, Bo; Feng, Ping; Lv, Keji; Yuan, Wenchao; Zhang, Panpan; Zhou, Chenyang
Abstract: Over the last 30 years, great progress has been made in the theory and applications of fluidized bed. However, very few studies haves addressed the change regulation of wall pressure during the fluidization process of magnetite powder. Pressure fluctuation is a key factor that affects the fluidization characteristic and separation effect. In the proposed work, theories about generation and propagation of pressure fluctuation had been discussed for better understanding the correlation between pressure fluctuation and the extent of fluidization as well as the particle motion behavior of magnetite powder. Simultaneously, a pressure measuring and analysis system was established to measure and analyzed pressure data in air dense medium fluidized bed, including a fluidized bed with measuring ports, air supply system, pressure sensor, data acquisition block and data processing block. Pressure sensor and data acquisition block make it easy to acquire precise pressure information. Based on MATLAB software, wavelet analysis was employed for pressure signals filtering and noise removing. Through systemic experimental study, it is proved that effective analysis results have obtained.